IMPLEMENTATION OF THE T SCHOOL PLAY MODEL LEARNING PROGRAM EARLIER (KINDERGARTEN) JOHOR BAHRU MALAYSIA - Filzah Julianti Iskandar (Journal of Educational Science Learning and Research, 2024)
The role of the Tadika (kindergarten) Udhatul Athfal educational institution is very strategic in preparing a generation of Muslims with reliable qualities through learning using a play model. The formulation of the research problem is: how is the play model used as a learning strategy at Tadika? The reason for using the play model in learning at Tadikaa? Meanwhile, the aim of this research is to determine the use of play models as a learning strategy, and the reasons for using play models and the purpose ofThe use of the play model as a learning strategy for Tadika (kindergarten) students takes place inside and outside the classroom. Learning with a play model in the classroom according to the main material, and outside the classroom also creates relaxation and expands children's activities so that they don't get bored if children only study in class.The reason for using the play model for students is according to the teacher's direction by playing with Lego, donut rings and toy cars. The use of play equipment as described occurs by individual students, playing together, or in groups. Meanwhile, the aims and benefits of using playing models with rattles, angklung, drums, puzzles, Lego, disassembly, plastic balls and cans, swings and slides. The aim is to maximize students' physical growth according to their age, and encourage students' psychological development regarding emotional and social matters, improve children's language skills, children's fine and gross motor skills, and improve social-emotional abilities when playing.